HCV evasion of IFN-alpha signalling : implications for therapy - Bourke, Nollaig (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Successful anti-viral immunity is dependent on effective activation of the innate immune response. The majority of individuals infected with hepatitis C virus (HCV) fail to eliminate the virus and progress to chronic infection. Treatment for HCV is with the anti-viral cytokine interferon-alpha (IFN-a), a potent activator of the innate immune system. Treatment response rates vary depending on viral genotype, with genotype 1 infected patients having response rates of less than 50%. IFN-a signals through the Janus kinase/Signal Transducers and Activators of Transcription (JAK/STAT) pathway, specifically activating STAT1, STAT2 and STAT3, which induces many IFN stimulated genes (ISGs). Studies from our group showed that STAT1 and STAT3 expression is reduced in peripheral blood mononuclear cells (PBMCs) from HCV patients. Therefore, our central hypothesis was that HCV directly inhibits IFN-a signalling, thus blocking anti-viral immune responses. We also proposed that in vitro expression of IFN-a induced ISGs would predict clinical responsiveness.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin